MUSYARAKAH PADA HARTA BERSAMA - Nadia Nadia; Noval Noval (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
The concept of marital property is still an interesting topic to discuss. Because there is still a disagreement between the concept of marital property to described by contemporary scholars through the approach of syirkah and the financial reality of today's family in Indonesia. This is because syirkah mufawadhah and syirkah 'abdan which explain is the type of syirkah 'uqūd that requires ijab-kabul and its provision for business. While in the context of marital property this concept is not achieved. Because the concept of marital property in Indonesia is more suitable towards the concept of syirkah amlak that does not require ijab-kabul and non-business. However, if want to conform to the concept of syirkah 'uqūd or syirkah business then there needs to be an improvement that must be preceded by a syirkah agreement or a contractual agreement on joint property either before marriage on premarital agreement or during marriage.